التبادلية في فن الخزف لتحقيق النحت الخزفي المعاصر - باهميم، هالة بنت أحمد Bahmeem, Hala Bent Ahmed (الجمعية العربية للحضارة والفنون الإسلامية, 2018)
The concept of reciprocity in ceramic art besides the method and technique of the clay material and the conversion of its sculpture properties, as ideas for designs that are employed in the production of ceramic sculptures through building ceramic piece of art owing interactive elements that makes its 3D structure compatible and formally balanced, revealing new features that opens advanced horizons to develop the artistic vision of the contemporary ceramics. This could be achieved through its use by the method of fitting the elements of the art form to create new artistic variable capable to be used as ceramic sculptures in a way showing the intellectual, technical, formulation and constructivism aspects of the ceramic art and to be an initiative for its concepts and contents understanding. Due to the scarcity of studies in this field, the scientific research problem assured that the beneficiary from the reciprocity between the ceramic form elements in implementation of ceramic sculpture is low , which has made our research aims to reach the most important structural foundations for interactive shape elements to produce a contemporary ceramic sculptures, That is why this research came in four chapters, chapter I of which illustrate the problem, the research importance, the need for its results and how to achieve the research goal and then the terms that are directly related to the title and purpose of the research. Chapter II dealt with the theoretical framework, it came in two parts to prove in the first part of it "reciprocity between arts" in the second part dealing with "The evolution and characteristics of porcelain". Chapter III, monitored related research and information to our results through several samples that were our research borders that relied on the descriptive, analytical curriculum. Finally the conclusion came assuring the research goal, chapter IV included the research results besides several recommendations and suggestions followed by the Arabic and foreign references list.
يعد مفهوم التبادلية في فن الخزف بالإضافة إلى أسلوب وتقنية الخامة الطينية وتحويل خوصها الخزفية بمثابة أفكار لتصميمات يتم توظيفها في إنتاج منحوتات خزفية وذلك ببناء أعمال خزفية تمتلك من العناصر التبادلية ما يجعلها ثلاثية الأبعاد في توافق وتوازن شكلي يكشف عن خصائص جديدة تفتح آفاقاً متطورة لبلورة الرؤية الفنية للخزف المعاصر، وذلك من خلال استخدامه بأسلوب تركيب عناصر الشكل الفني لإنشاء متغير فني جديد يرتقي إلى مستوى توظيفه كمنحوتات خزفية بصياغة تظهر الجوانب الفكرية والتقنية والبنائية والشكلية لفن الخزف وتكون بداية لاستيعاب مفاهيمه ومضامينه المعاصرة. ونظرا لندرة الدراسات في هذا الاتجاه، تأكدت مشكلة البحث في قلة الاستفادة من التبادلية بين عناصر الشكل الخزفي في تنفيذ النحت الخزفي، وهذا ما جعل البحث يهدف إلى التوصل لأهم الأسس البنائية لتبادلية عناصر الشكل لإنتاج منحوتات خزفية معاصرة، لذلك جاء هذا البحث في أربعة فصول، تناول الفصل الأول منه توضيح مشكلة البحث وأهميته والحاجة إليه وكيفية تحقيق هدفه ثم المصطلحات التي لها علاقة مباشرة بعنوان البحث وهدفه، أما الفصل الثاني فقد تناول الإطار النظري، فجاء في جزئين ليثبت في الجزء الأول منه "التبادلية بين الفنون" وفي الجزء الثاني تناول "تطور الخزف وخصائصه" أما الفصل الثالث فرصد مجتمع البحث والمعلومات المتعلقة به من خلال عدة عينات، كانت هي حدود البحث الذي اعتمد على المنهج الوصفي. التحليلي. ثم جاءت الاستنتاجات مؤكدة لهدف البحث وقد ضم الفصل الرابع نتائج البحث وعدد من التوصيات والمقترحات تليها قائمة المراجع العربية والأجنبية.
Keywords: النحت الخزفى المعاصر; الخزف العراقى المعاصر; التبادلية; فن الخزف